Understanding Congenital FXI Deficiency: Genetic Diagnosis and Correlation of Variant Detection Rate to Factor XI Activity - Pezeshkpoor, Behnaz; Banchev, Atanas; Preisler, Barbara; Scholz, Ute; Zieger, Barbara; Oldenburg, Johannes; Pavlova, Anna (Hämostaseologie, 2025)
Factor XI (FXI) deficiency is an autosomal bleeding disorder characterized by low FXI levels, resulting in bleeding after trauma or surgery. Genetic variants affecting FXI structure and function often result in bleeding diatheses.This study aimed to estimate the variant detection rate (VDR), and assess its correlation with FXI activity (FXI:C) in a large cohort of FXI-deficient patients.Genetic defects in the F11 gene were analyzed in 316 index patients (IPs) using Sanger or next-generation sequencing. Multiplex ligation-dependent probe amplification or copy number variation analysis was used to detect duplications and deletions.Genetic defects were identified in 249 IPs (VDR of 79%). A strong negative correlation (Pearson coefficient: −0.891) was found between FXI:C levels and VDRs: higher FXI:C levels corresponded to a lower likelihood of detecting genetic alterations, with a significant decline in VDR beyond 60 IU/dL. A total of 286 genetic variants were identified in F11 gene: 56% missense, 24% nonsense, 11% small deletions/insertions, and 6% splice-site variants. Large deletions were rare (3%). A total of 48 novel variants were detected. Ashkenazi Jewish founder variants were the most frequent (14.3%). Variants p.Gln134Ter, p.Ile215_Asp216del, and p.Glu315Lys (27% of cases) were recurrent. In four cases, large deletions extended beyond the F11 gene and included the neighboring KLKB1 gene, encoding prekallikrein.This study demonstrated a significant negative correlation between FXI:C levels and VDRs, underscoring the importance of genetic testing. Findings included combined deficiencies in FXI and prekallikrein due to large deletions affecting both F11 and KLKB genes.
Keywords: FXI deficiency; bleeding; genetic analysis; F11 gene; KLKB1 gene